THE RELATIONSHIP BETWEEN KNOWLEDGE LEVELS AND ADOLESCENTS' ATTITUDES ABOUT PREVENTION OF HIV/AIDS IN GLOBAL WHITE LOTUS ISLAMIC HIGH SCHOOL - Fitria, Erika; Arabta M. Peraten Pelawi; i, Riris Ocktaryna Silitonga (Rena Cipta Mandiri, 2023)
Adolescence is a period of transition from childhood to adulthood. Adolescence is the age of majority who are considered vulnerable to infection due to lack of knowledge about the dangers of HIV/AIDS. Hormonal changes in late adolescence will increase sexual desire. The tendency of violations or deviations in sexual behavior will increase due to the dissemination of information through the mass media. Intercourse will also increase and it cannot be denied that the tendency of association between men and women at that age will increase the risk of deviations in sexual behavior which can increase the risk of getting HIV/AIDS.